Aplikacija posebnega prenosnega sedeža na podvozju - predstavitev primera - Rotar, Eli (Rehabilitacija (Ljubljana), 2013)
Abstract We describe an example of equipping a patient with a very severe form of cerebral palsy with a custom made seating unit mounted on a special frame, produced using a computer model. The prescription and the application of such a technical aid can only be performed by an experienced interdisciplinary rehabilitation team with sufficient medical and technical knowledge and experience in prescription of technical aids. When choosing the most appropriate seating unit it is necessary to take into account the impairment of body structures and functions, the users participation in activities of daily living, the level of the assistance he/she needs and the environment in which he/she lives. The article presents the entire process of the application from testing, making the design, manufacturing and intermediate tests to the final application of the device.
Keywords: Cerebral palsy; cerebralna paraliza; individually made seating unit; medicinska oprema; prenosni sedež; rehabilitation team; seating unit mounted on a frame